Improving Coherence In Paragraph Writing Among ESL Learners: A Case Study - Hamzah, Masputeriah; Karuppiah, Malini (2010)
This study sets out to examine the problems faced by ESL learners of the Faculty of Education,UTM in relation to coherence in writing. The objectives of this study are to assess the coherence of ESLlearners’ writing as well as to present ideas and suggestions to help students to improve coherence in theirwriting. Ten first year TESL students of UTM were involved in this study. The instrument used to assessand analyze coherence in writing was topic-based analysis adapted from Todd (2004). Scores ofcoherence and coherence breaks as well as interviews were used for data analysis. Finally, this study hopes to be a valuable resource for not only the learners to overcome incoherence in their writing, but also to both content and English language instructors of these learners. It would provide insights to the language teachers on how to help students become more aware of elements of coherence in writing and what can be done to improve coherence in writing.